2020
DOI: 10.5194/tc-2020-65
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inter-comparison of snow depth over sea ice from multiple methods

Abstract: Abstract. In this study, we compare eight recently developed snow depth products that use satellite observations, modeling or a combination of satellite and modeling approaches. These products are further compared against various ground-truth observations, including those from ice mass balance buoys (IMBs), snow buoys, snow depth derived from NASA's Operation IceBridge (OIB) flights, as well as snow depth climatology from historical observations. Large snow depth discrepancies between the different sno… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Kwok and Maksym (2014) found that snow depths sampled in situ may be biased due to excessively thin and thick ice not being logistically feasible to sample, while radar-based measurements cannot resolve snow depths below 8 cm, and often have poor returns around deformed ice. Zhou et al (2020) recently showed that different models for snow depth can give high variations for snow density and depth, and in some cases this can be higher than climatology. Similarly, Mallett et al (2020) showed that assuming a constant snow density, and hence a constant radar penetration speed, biases the snow depth estimate.…”
Section: Snow On Sea Icementioning
confidence: 99%
“…Kwok and Maksym (2014) found that snow depths sampled in situ may be biased due to excessively thin and thick ice not being logistically feasible to sample, while radar-based measurements cannot resolve snow depths below 8 cm, and often have poor returns around deformed ice. Zhou et al (2020) recently showed that different models for snow depth can give high variations for snow density and depth, and in some cases this can be higher than climatology. Similarly, Mallett et al (2020) showed that assuming a constant snow density, and hence a constant radar penetration speed, biases the snow depth estimate.…”
Section: Snow On Sea Icementioning
confidence: 99%
“…Kwok and Maksym [9] found that snow depths sampled in situ may be biased due to excessively thin and thick ice not being logistically feasible to sample, while radar-based measurements cannot resolve snow depths below 8 cm. Zhou et al [13] recently showed that different models for snow depth can give high variations for snow density and depth, and in some cases this can be higher than climatology. Similarly, Mallett et al [14] showed that assuming a constant snow density, and hence a constant radar penetration speed, biases the snow depth estimate.…”
Section: Introductionmentioning
confidence: 99%